Towards a practice-based approach to public innovation – Apollonian and Dionysian practice-approaches - Fuglsang Lars (Nordic Journal of Social Research)
This paper discusses how a practice-based approach to public innovation can provide an alternative, critical means of looking at public innovation. It unravels two ways practices can exist in relation to public innovation: Apollonian and Dionysian practiceapproaches. The Apollonian practice-approach is purposeful, speaking of the actors’ plans and interests and the rules of the game. In contrast, the Dionysian is a more spontaneous, bricolage-like approach to innovation that gathers people in an open space of innovation. Given these contrasting approaches further illustrated through two case vignettes, the paper argues that public innovation transpires not only through purposeful practices and plans but also more contextual public services changes. Research needs to capture both of these approaches and explore their impact on innovation. The paper concludes by outlining a research strategy for investigating practice-approaches in public service innovation and how a practice-based approach can add to our understanding of public service innovation.